Evaluation of the effect of erenumab on migraine‐specific questionnaire in patients with chronic and episodic migraine - Po‐Wei Chen; Mats O. Karlsson; Sebastian Ueckert; Ari Pritchard‐Bell; Cheng‐Pang Hsu; Sandeep Dutta; Malidi Ahamadi (CPT: Pharmacometrics & Systems Pharmacology, 2023)
Abstract Erenumab is a fully human anti‐canonical calcitonin gene‐related peptide receptor monoclonal antibody approved for migraine prevention. The Migraine‐Specific Quality‐of‐Life Questionnaire (MSQ) is a 14‐item patient‐reported outcome instrument that measures the impact of migraine on health‐related quality of life. Erenumab data from four phase II/III clinical trials were used to develop an item response theory (IRT) model within a nonlinear mixed effects framework, (i) evaluate the MSQ item information with respect to patient disability, (ii) characterize the longitudinal progression of the MSQ, and (iii) quantify the effect of erenumab on the MSQ in patients with migraine. The majority (80%) of information was found to be contained in 9 out of 14 items, extending the current knowledge on the reliability of the MSQ as a psychometric tool. Simulations across three MSQ domains show significant improvement from baseline, exceeding minimally important differences. Overall, the IRT model platform developed herein allows for systematic quantification of the effect of erenumab on the MSQ in patients with migraine.